1992
DOI: 10.1111/j.1532-5415.1992.tb02108.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Influenza A (H3N2) in a Well Immunized Nursing Home Population

Abstract: While antigenic drift of the circulating influenza virus was the major factor in the apparent vaccine failure, the observed poor staff immunization rate (10%) and absence of surveillance which precluded the use of amantadine chemoprophylaxis suggest that the use of these strategies may be of importance in controlling influenza outbreaks in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 32 publications
1
74
0
3
Order By: Relevance
“…[213] Also in contrast to the Cochrane findings, several studies have reported that vaccination can be up to 80% effective in preventing influenza-related mortality. [211,[214][215][216] Additionally, a study looking at the populationlevel impact of a vaccination program in Sao Paulo, Brazil detected a 26% reduction in age-specific influenza-attributable mortality following the introduction in 1998 of funding for annual mass vaccination campaigns for adults aged ≥65 years. [217] The effects of vaccination may vary between community-dwelling and institutionalized elderly populations.…”
Section: Vaccine Performancementioning
confidence: 99%
“…[213] Also in contrast to the Cochrane findings, several studies have reported that vaccination can be up to 80% effective in preventing influenza-related mortality. [211,[214][215][216] Additionally, a study looking at the populationlevel impact of a vaccination program in Sao Paulo, Brazil detected a 26% reduction in age-specific influenza-attributable mortality following the introduction in 1998 of funding for annual mass vaccination campaigns for adults aged ≥65 years. [217] The effects of vaccination may vary between community-dwelling and institutionalized elderly populations.…”
Section: Vaccine Performancementioning
confidence: 99%
“…High immunisation rates may result in herd immunity, involving increased protection for all residents, including the weakest amongst them (Coles et al, 1992;Drinka et al, 1997;Fox et al, 1971). Moreover, realising herd immunity may be the best way to prevent an influenza outbreak that will have devastating effects on daily life and care within the institution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of immunisation among residents is not the only relevant factor for herd immunity. Immunisation of health care workers is also important, because of their possible role in introducing and spreading the virus among the nursing homes (Carman et al, 2000;Coles et al, 1992;Drinka et al, 1997;Fox et al, 1971;Nicholson, 2000;Potter et al, 1992). We have no data about the level of immunisation of health care workers in Dutch nursing homes, but, apparently, occupational immunisation is not given high priority: only 21.6% of the responding institutions in our survey explicitly request their personnel to get vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of patients who are particularly at risk of hospital epidemics are residents of facilities, which render care and treatment services for patients with chronic illnesses. During the occurrence of an inluenza outbreak in a facility whose residents were at the age of above 65 years, the percentage of infected patients in an epidemic season was very high and it could reach even 60% [68]. The facts that inluenza vaccinations in the elderly are not as efective as vaccinations in a younger population (30-40% vs 70-90%), and that inluenza epidemics occurred in the populations of the residents of nursing homes, where inluenza immunization was very high and reached even 90%, prove that it is necessary to perform vaccinations in healthcare professionals in order to protect the patients [69,70].…”
Section: A Local Commitee For Hospital Infections Decided To Conduct mentioning
confidence: 99%